Long-Term Adaptation : Selecting Farm Types across Agro-Ecological Zones in Africa - Seo, Niggol; Mendelsohn, Robert; Dinar, Ariel; Kurukulasuriya, Pradeep; Hassan, Rashid (World Bank, Washington, DC, 2012)
Using economic data from more than 8,500 household surveys across 10 African countries, this paper examines whether the choice of farm type depends on the climate and agro-ecological zone of each farm. The paper also studies how farm type choice varies across farmers in each zone, using a multinomial logit choice model. Farmers are observed to choose from one of the following five types of farms: rainfed crop-only, irrigated crop-only, mixed rainfed (crop and livestock), mixed irrigated, and livestock-only farming. The authors compare current decisions against future decisions as if the only change were climate change. They focus on two climate scenarios from existing climate models: the Canadian Climate Centre scenario, which is hot and dry, and the Parallel Climate Model scenario, which is mild and wet. The results indicate that the change in farm types varies dramatically by climate scenario but also by agro-ecological zone. Policy makers must be careful to encourage the appropriate suite of measures to promote the most adapted farm type to each location.